Low-loss AgReMo2O8 (Re = Y, Yb) LTCC ceramics designed by Ag+ common-ion effect for dielectric resonator antenna applications - Jian Bao; Jing Guo; Da Tian; Zhen Fang; Zhen-Tao Wang; Yang Liu; Yang Gao; Cai-Hong Zhang; Biao-Bing Jin; Andreu Cabot; Li-Xia Pang; Kar Ban Tan; et al. (Chemical Engineering Journal, 2026)

Corrigendum to ‘Wavelength-dependent photobiomodulation attenuates synovial inflammation in fibroblast-like synoviocytes and a collagenase-induced osteoarthritis model’ [Journal of Photochemistry & Photobiology B: Biology Volume 272 (2025) 113276] - Tianxiang Fan; Peng Xia; Safayet Ahmed; Yuen H. Tsang; Zhi Yao; Deli Wang; Ziyu Chen; Lixiang Xue; Dongquan Shi; Bo Wang; Chi Fai Cheung; Marco Y.C. Pang; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

A hybrid machine-learning and process-based regional crop modelling framework to improve rice production strategies under data constraints - Qiang Li; Xia Liang; Maofang Gao; Yunrui Li; Ian R. Willett; Helen Suter; Alexis Pang; Mengxuan Zhang; Phetmanyseng Xangsayasane; Zhiyuan Wang; Deli Chen (Computers and Electronics in Agriculture, 2026)

Role of organic acid structure in modulating the hygroscopicity and efflorescence kinetics of ammonium sulfate - Li Xia; Shufeng Pang; Qishen Huang; Yunhong Zhang (Journal of Environmental Sciences, 2026)

Characteristics and Mechanisms of Crack Propagation in Gas-Bearing Coal Under Adsorptive Versus Non-Adsorptive Gas Conditions - Dengke Wang; Yixuan Tang; Wenrui Li; Hongtu Zhang; Biao He; Furu Kang; Shixing Fan; Baisheng Nie; Yuling Xia; Xiaofei Pang; Jinhao Yu (Natural Resources Research, 2026)

Electrochemical conversion of salinity gradient energy by conjugated carbonyl polyanthraquinone imides - Nan-Sen Zhou; Wei-Bin Zhang; Ashkar Batol; Xia-Yue Yuan; Qin-Fang Wang; Jun Pang; Huan Gou; Jia-Xin Li; Xue-Jing Ma (Chemical Engineering Journal, 2026)

Strongly spatial-confined self-assembled monolayers for high-performance perovskite photovoltaics - Dongyang Li; Qiming Yin; Zhiwei Ren; Guihua Zhang; Jie Li; Qianyi Li; Yu Han; Sibo Li; Lihan Pang; Hao Xia; Guang Yang; Longbin Qiu; et al. (Science Bulletin, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

From biomass to supercapacitor electrode materials: bamboo derived carbon decorated with MnO2 used in flexible energy storage device - Pengfei Jia; Binyang Liu; Shenao Li; Yizhan Sun; Shuwen Lv; Ru Liu; Yuandong Xu; Xia Zhang; Wei Kong Pang; Peng Li (Fuel, 2026)

Effect of palladium loading on catalytic performance and product selectivity during diclofenac degradation by Pd0@anaerobic activated sludge - Xiaodi Li; Jingzhou Zhou; Lin Yang; Si Pang; Yi Yang; Defu Gan; Junxia He; Penghui Shi; Siqing Xia (Journal of Cleaner Production, 2026)

Synergistic enhancement of photocatalytic activity via oxygen vacancy engineering in a CPDs/Vo-BiOCl Z-scheme heterostructure - Zhiyuan Pang; Bin Wang; Taiquan Yang; Xingwang Yan; Jiexiang Xia; Huaming Li (Journal of Environmental Chemical Engineering, 2026)

Comparative effects of ultra-high pressure, ultra-high temperature, and thermal pasteurization processing on the flavor characteristics and nutritional components of freshly squeezed Hami melon juice - Jinxiao Cheng; Yining Xia; Xinli Geng; Lingling Pang; Di Shen; Limei Li; Yifan Gu; Yanfang Pan (Food Chemistry, 2026)

Intratracheal perfluorooctane sulfonate induces pulmonary injury via TLRs signaling and disrupts sex steroidogenesis through systemic translocation - Yuwei Chen; Dan Xu; Guanhua Pang; Fanmei Zeng; Yuan Sun; Qing Xia; Luwei Zhao; Yifei Li; Wen Peng; Miao He (Environmental Pollution, 2026)

Atractylenolide III alleviates amyloid-β-induced cognitive impairments in mice - Hao Yuan; Lei Xia; Junjie Li; Chunfang Dai; Xiaohuan Li; Boqing Xu; Mengtong Xue; Xiuyu Shi; Bin Wu; Zhifang Dong; Yayan Pang (Molecular Biology Reports, 2025)

The Association between Dietary and Circulating Copper Levels and Osteoporosis: a Scoping Review - Ye Ju; Wei Xiong; Yuqi Pang; Zilan Chen; Jiaojiao Hou; Sirui Zheng; Zihao Li; Ting Liu; Hongxia Xia; Maoyao Xia; Yangdan Zhong; Jiayuan Li; et al. (Biological Trace Element Research, 2025)
Copper plays a crucial role in osteoporosis by regulating osteoblast function, inhibiting osteoclast activity, and promoting bone matrix maturation. However, the epidemiological relationship between copper and osteoporosis remains inconclusive. This scoping review systematically examined the existing evidence on the association between dietary and circulating copper levels and bone related diseases with a special focus on osteoporosis. Studies were identified through comprehensive search of electronic databases from inception to January 2025. Eligible studies included randomized clinical trials, cohort studies, case-control studies, and cross-sectional studies involving human subjects and published in English. The review included 18 studies. For dietary copper, studies reported that higher intake was associated with improved bone mineral density (BMD). For circulating copper, studies reported that lower levels were associated with higher subsequent risk of osteoporosis and fractures. For environmental copper, exposed via drinking water or hair copper levels were not associated with osteoporosis. Current evidence on the relationship between copper and bone health remains largely consistent, suggesting a potential inverse association between copper levels and osteoporosis risk.

Wavelength-dependent photobiomodulation attenuates synovial inflammation in fibroblast-like synoviocytes and a collagenase-induced osteoarthritis model - Tianxiang Fan; Peng Xia; Safayet Ahmed; Yuen H. Tsang; Zhi Yao; Deli Wang; Ziyu Chen; Lixiang Xue; Dongquan Shi; Bo Wang; Chi Fai Cheung; Marco Y.C. Pang; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

Varied influence of aged microplastics and related leachates on phosphorus transformation and release from the sediments - Wenjuan He; Jinhui Huang; Si Liu; Enjie Li; Jinying Hu; Haoliang Pang; Zhexi Liu; Xia Wang; Yuanyuan Li; Xue Li (Journal of Hazardous Materials, 2025)

Metagenomic insights into a solid phase heterotrophic-autotrophic denitrification reactor driven by biodegradable polymers and pyrite - Yunmeng Pang; Lin Xia; Shengjie Li; Jianlong Wang; Hai Lin (Journal of Cleaner Production, 2025)

Single-pot biocatalytic valorization of agricultural waste into high fructose syrup via synergistic deep eutectic solvent and enzyme engineering - Yong Zhi; Xingjun Lu; Li Pang; Liwen Jiang; Hong Tian; Xiao Chen; Bo Xia (Chemical Engineering Journal, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Network Pharmacology and Experimental Evidence Identify the Mechanism of Astragaloside IV against Henoch-Schönlein Purpura Nephritis - Shuang Pang; Qinghao Yan; Haiou Xia; Shaowei Liu; Feifei Gu; Yan Xu; Min Li; Liping Yue (Cell Biochemistry and Biophysics, 2025)

Surface passivated 3D halide perovskite single crystal by 2D perovskite towards high performance soft X-ray detection and gamma-ray spectrum - Yan Xiong; Min Li; Shunsheng Yuan; Yuting Liu; Tong Jin; Jincong Pang; Sihao Xia; Mingquan Liao; Lingling Liu; Lingfeng Wu; Kuan Yew Cheong; Huayang Yu; et al. (Chemical Engineering Journal, 2025)

Self-assembled gallic acid-rare earth nanocomplexes against MRSA with multi-targeting antibacterial mechanisms robustly combating bacterial resistance - Xian Liu; Qiwu Yuan; Yang Yang; Ke Li; Nanjiong Pang; Jiangtao Wang; Ming Yang; Xia Li; Junling Guo; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2025)

Synergistic role of deep eutectic solvents in improving engineered chitinase activity for insoluble chitin hydrolysis - Xiao Chen; Li Pang; Wentao Yang; Hong Tian; Jinghan Wang; Liang Yang; Bo Xia (Food Bioscience, 2025)

Microbial synergy mechanism of hydrogen flux influence on hydrogen-based partial denitrification coupled with anammox in a membrane biofilm reactor - Si Pang; Xiang Cai; Lin Yang; Jingzhou Zhou; Xiaodi Li; Siqing Xia (Environmental Research, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Microglia programmed cell death in neurodegenerative diseases and CNS injury - Ling Cai; Qiuyue Fan; Rui Pang; Chen Chen; Yueman Zhang; Haiyi Xie; Jingyi Huang; Yu Wang; Peiying Li; Dan Huang; Xia Jin; Yuxi Zhou; et al. (Apoptosis, 2025)

Unveiling additive-driven crystallization-kinetics control for efficient ultrapure red perovskite light emitting diodes - Tao Sheng; Yulin Mao; Jia Guo; Guangbao Wu; Junmin Xia; Zhipeng Zhang; Bingzhe Wang; Shengwen Li; Peiyuan Pang; Miao Zeng; Wei Hong; Dejian Yu; et al. (Chemical Engineering Journal, 2025)

The impeded film-formation kinetics with ameliorated carrier trap density to construct efficient as-cast organic solar cells through short multi-branched alkylthio chains strategy - Ling Li; Na Li; Jiefeng Hai; Shenzheng Gao; Hao Xu; Ming Luo; Xinjie Zhou; Xiaoyu Shi; Shanlei Xu; Xueming Li; Zhenhuan Lu; Youyong Pang; et al. (Chemical Engineering Journal, 2025)

Control of membrane biofouling in MBR for wastewater treatment by biohybrid membrane with superhydrophilic self-QQ function - Haoliang Pang; Jinhui Huang; Xue Li; Kaixin Yi; Zhexi Liu; Xia Wang; Wei Zhang; Chenyu Zhang; Si Liu (Journal of Environmental Chemical Engineering, 2024)

The Lotus corniculatus MYB5 functions as a master regulator in proanthocyanidin biosynthesis and bioengineering - Wenbo Jiang; Qian Li; Yaying Xia; Yinuo Yan; Shiyao Yue; Guoan Shen; Yongzhen Pang (Plant Cell Reports, 2024)

Salinomycin, a potent inhibitor of XOD and URAT1, ameliorates hyperuricemic nephropathy by activating NRF2, modulating the gut microbiota, and promoting SCFA production - Yong-jun Chen; Zi-tao Guo; Hai-qiao Chen; Shi-fan Zhang; Ying-xia Bao; Zhoufan Xie; Jia-le Ke; Wen-jie Ye; Jia-cheng Liang; Jia-chen Chen; Ning Li; Feng-xin Zheng; et al. (Chemico-Biological Interactions, 2024)

Enhanced degradation of insoluble chitin: Engineering high-efficiency chitinase fusion enzymes for sustainable applications - Xiao Chen; Li Pang; Wentao Yang; Hong Tian; Youjin Yi; Bo Xia (Bioresource Technology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

High-performance carboxymethyl starch/PVA based intelligent packaging films engineered with Cu-Trp nanocrystal as functional compatibilizer - Ruoyi Xu; Lijun Xia; Qun Tang; Fushun Tang; Shiyi Pang; Heping Li; Zhiming Zou (Food Chemistry, 2024)

Injectable hydrogels for bioelectronics: A viable alternative to traditional hydrogels - Qianhe Shu; Yuzhe Gu; Wenjie Xia; Xiaomin Lu; Yuncong Pang; Junchen Teng; Baoguang Liu; Yang Li (Chemical Engineering Journal, 2024)

Aberrant expression of LGALS3BP drives an unfavorable prognosis and more aggressive in HCC via regulating PI3K/AKT signaling - Yang Liu; Lei Liang; Jian Li; Tao Pang; Shu Hong Zhang; Zhang Yong Xia (Tissue and Cell, 2024)

The role of DsbA and PepP genes in the environmental tolerance and virulence factors of Cronobacter sakazakii - Tong Jin; Liuxin Pang; Ting Yue; Lingling Niu; Tingting Li; Yujing Liang; Yunlong Zhang; Chunhong Yan; Baowei Yang; Chunling Zhang; Xiaodong Xia (Food Research International, 2024)

An overview of quorum sensing in shaping activated sludge forms: Mechanisms, applications and challenges - Xia Wang; Kaixin Yi; Haoliang Pang; Zhexi Liu; Xue Li; Wei Zhang; Chenyu Zhang; Si Liu; Jinhui Huang; Chen Zhang (Science of The Total Environment, 2024)

A Combined Manual Annotation and Deep-Learning Natural Language Processing Study on Accurate Entity Extraction in Hereditary Disease Related Biomedical Literature - Dao-Ling Huang; Quanlei Zeng; Yun Xiong; Shuixia Liu; Chaoqun Pang; Menglei Xia; Ting Fang; Yanli Ma; Cuicui Qiang; Yi Zhang; Yu Zhang; Hong Li; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2024)
We report a combined manual annotation and deep-learning natural language processing study to make accurate entity extraction in hereditary disease related biomedical literature. A total of 400 full articles were manually annotated based on published guidelines by experienced genetic interpreters at Beijing Genomics Institute (BGI). The performance of our manual annotations was assessed by comparing our re-annotated results with those publicly available. The overall Jaccard index was calculated to be 0.866 for the four entity types—gene, variant, disease and species. Both a BERT-based large name entity recognition (NER) model and a DistilBERT-based simplified NER model were trained, validated and tested, respectively. Due to the limited manually annotated corpus, Such NER models were fine-tuned with two phases. The F1-scores of BERT-based NER for gene, variant, disease and species are 97.28%, 93.52%, 92.54% and 95.76%, respectively, while those of DistilBERT-based NER are 95.14%, 86.26%, 91.37% and 89.92%, respectively. Most importantly, the entity type of variant has been extracted by a large language model for the first time and a comparable F1-score with the state-of-the-art variant extraction model tmVar has been achieved. Graphical Abstract

Panax quinquefolius saponins and panax notoginseng saponins attenuate myocardial hypoxia-reoxygenation injury by reducing excessive mitophagy - Junyan Xia; Cong Chen; Yanan Sun; Sinai Li; Yuxuan Li; Bai-Ru Cheng; Yanting Pang; Yan Li; Dong Li; Qian Lin (Cell Biochemistry and Biophysics, 2024)

Enhanced removal of 2,4-dichlorophenol by coupling of Pd nanoparticles with biofilm - Chengyang Wu; Jingzhou Zhou; Si Pang; Lin Yang; Xiaodi Li; Eric Lichtfouse; Siqing Xia; Hongbo Liu (Journal of Environmental Chemical Engineering, 2024)

Semi-interpenetrating network hydrogels-based microcapsule for quorum quenching bacteria biocontainment to enhance biofouling control in membrane bioreactor - Kaixin Yi; Jinhui Huang; Haoliang Pang; Suzhou Li; Zhexi Liu; Xia Wang; Wei Zhang; Chenyu Zhang; Si Liu; Yanling Gu (Chemical Engineering Journal, 2024)

Multi-media distribution and risk assessment of per- and polyfluoroalkyl substances in the Huai River Basin, China - Yanru Tao; Yan Pang; Mingke Luo; Xia Jiang; Jiahao Huang; Zechan Li (Science of The Total Environment, 2024)

A decadal atmospheric ammonia reanalysis product in China - Bufan Xu; Jianbing Jin; Li Fang; Mijie Pang; Ji Xia; Baojie Li; Hong Liao (Science of The Total Environment, 2024)

Chronic exposure to polystyrene microplastics increased the chemosensitivity of normal human liver cells via ABC transporter inhibition - Zihan Chen; Yue Li; Honghuan Xia; Yuanyuan Wang; Shaochen Pang; Chunyan Ma; Lei Bi; Fengbang Wang; Maoyong Song; Guibin Jiang (Science of The Total Environment, 2024)

Efficient electro-demulsification of O/W emulsions and simultaneous oil removal enabled by a multiscale porous biocarbon electrode - Kui Wang; Hailiang Zhao; Yingming Zhang; Xu Li; Mengyi Xu; Meirong Song; Guangxin Ru; Xiaolei Jiang; Xiuhong Zhu; Dandan Han; Yutao Dong; Kexin Shen; et al. (Chemical Engineering Journal, 2024)

Hydrophobic electrospun membrane of peppermint oil loaded zein with coating of methyltriethoxysilane for active packaging - Li Xia; Linlin Li; Yewen Xiao; Feng Xiao; Wei Ji; Min Pang; Hualin Wang (Food Hydrocolloids, 2023)

The interplay of sulfate and nitrate triggers abiotic reduction in a hydrogen-based membrane biofilm reactor for antimonate removal - Jingzhou Zhou; Chengyang Wu; Si Pang; Lin Yang; Mengying Yao; Xiaodi Li; Siqing Xia; Bruce E. Rittmann (Chemical Engineering Journal, 2023)

Sensitivity and control efficacy of a novel complex III inhibitor pyribencarb against Sclerotinia sclerotiorum - Ang Li; Hongjie Liang; Xinyi Cui; Weixu Yang; Xin Zhou; Pengwen Zeng; Dingzhi Pang; Shenjv Xia; Hongying Shan; Ning Li; Jinli Li (Journal of Plant Diseases and Protection, 2023)

Surface engineering of Al2O3 nanotubes by ureasolysis method for activating persulfate degradation of antibiotics - Zheng-Wu Wang; Mei-Yun Xiao; Jun-Feng Tang; Ming-Qian Li; Xia-Yin Yin; Ting Wang; Yi-Zhou Zhu; Dai-Wen Pang; He-Fang Wang (Journal of Hazardous Materials, 2023)

Advances in molten-salt-assisted synthesis of 2D MXenes and their applications in electrochemical energy storage and conversion - Fei Wang; Shujuan Wang; Feng Tian; Fuqian Wang; Xuewen Xia; Qi Zhang; Zhongya Pang; Xing Yu; Guangshi Li; Hsien-Yi Hsu; Shen Hu; Li Ji; et al. (Chemical Engineering Journal, 2023)

Enrichment strategies of heavy metals in the O/H/O process composed of biological fluidized bed for wastewater treatment: A case study of Cu and Zn - Cong Wei; Xiaoqian Cheng; Wei Sun; Xia Tang; Tuo Wei; Zijun Pang; Xiong Ke; Zhi Qin; Jiamin Pan; Gengrui Wei; Guanglei Qiu; Chunhua Feng; et al. (Journal of Cleaner Production, 2023)

Ultrathin porous Bi2WO6 with rich oxygen vacancies for promoted adsorption-photocatalytic tetracycline degradation - Weihong Gao; Geng Li; Qiuwen Wang; Lijun Zhang; Kang Wang; Shaoxuan Pang; Guangming Zhang; Longyi Lv; Xiaoyang Liu; Wenfang Gao; Li Sun; Yuguo Xia; et al. (Chemical Engineering Journal, 2023)

Biological reduction and hydrodechlorination of chlorinated nitroaromatic antibiotic chloramphenicol under H2-transfer membrane biofilm reactor - Lin Yang; Si Pang; Jingzhou Zhou; Xiaodi Li; Mengying Yao; Siqing Xia (Bioresource Technology, 2023)

Ex vivo coronary endothelial cell activation associated with indoor coal combustion initiated atherosclerosis - Wanjun Zhang; Yaxian Pang; Wenting Cheng; Tao Wang; Yanting Li; Xin Li; Jianzhong Zhang; Xiaowen Xia; Yuxin Zheng; Rong Zhang; Jinglong Tang (Science of The Total Environment, 2023)

Biological conversion of sulfisoxazole in an autotrophic hydrogen-based membrane biofilm reactor - Lin Yang; Si Pang; Jingzhou Zhou; Chengyang Wu; Xiaodi Li; Mengying Yao; Siqing Xia; Bruce E. Rittmann (Journal of Water Process Engineering, 2023)

Simultaneous removal of nitrate and ammonium by hydrogen-based partial denitrification coupled with anammox in a membrane biofilm reactor - Si Pang; Yun Zhou; Lin Yang; Jingzhou Zhou; Xiaodi Li; Siqing Xia (Bioresource Technology, 2023)

Numerical simulation of fault deformation and seismic activity in the southern Qinghai–Tibet Plateau - Yuan Li; Xia Liu; Mikhail Rodkin; Yajin Pang (Journal of Seismology, 2022)

The Association of CTLA-4 rs231775 and rs3087243 Polymorphisms with Latent Autoimmune Diabetes in Adults: A Meta-Analysis - Haipeng Pang; Shuoming Luo; Gan Huang; Xia Li; Zhiguo Xie; Zhiguang Zhou (Biochemical Genetics, 2022)

Risk assessment and support design optimization of a high slope in an open pit mine using the jointed finite element method and discontinuous deformation analysis - Jingyu Kang; Daochun Wan; Qian Sheng; Xiaodong Fu; Xin Pang; Luqing Xia; De Li (Bulletin of Engineering Geology and the Environment, 2022)

A preliminary evaluation of the red seaweed Gracilariopsis silvana, isolated from Colon, Panama, as a potential new agar-producing cultivar - Mengjie Zhang; Hu Li; Junrui Xue; Tong Pang; Gloria Batista de Vega; Bangmei Xia; Jianguo Liu (Journal of Applied Phycology, 2021)

Acutely Rising Temperature Reduces Photosynthetic Capacity of Phytoplankton Assemblages in Tropical Oceans: A Large-Scale Investigation - Guangming Mai; Jihua Liu; Xiaomin Xia; Xinyue Pang; Binkai Li; Linghui Yu; Yehui Tan; Xingyu Song; Gang Li (Frontiers in Marine Science, 2021)
Climate changes interacting with human activities are raising the temperature in global oceans. To explore physiological responses of in situ phytoplankton assemblages to increasing temperatures, we conducted a shipboard experiment in tropical regions of the eastern Indian Ocean, Java Sea, and southern South China Sea. Throughout the surveyed areas, phytoplankton biomass (Chl a ) ranged from 0.09 to 0.86 μg L −1 (median, 0.22 μg L −1 ) in the surface and from 0.30 to 0.99 μg L −1 (median, 0.50 μg L −1 ) in maximal chlorophyll layer (DCM), respectively. Picophytoplankton that occupied 27–89% (79%) and 83–92% (88%) of total Chl a in the surface and DCM layers, ranged from 0.32 × 10 4 to 23.10 × 10 4 cells mL −1 (3.69 × 10 4 cells mL −1 ) and from 7.44 × 10 4 to 25.70 × 10 4 cells mL −1 (12.60 × 10 4 cells mL −1 ), respectively. Synechococcus took up 30–97% (78%) of pico-cells compositions in the surface layer, while, in the DCM layer, Prochlorococcus took up 42–98% (91%). Moreover, the maximal photochemical quantum yield (F V /F M ) of photosystem II (PS II) and the rapid light curve (RLC)-derived light utilization efficiency ( α ) were lower in the surface layer than that in the DCM layer, but the saturation irradiance (E K ) was higher. In particular, we found that acutely rising temperature decreased the F V /F M and α in both the surface and the DCM layers but increased the absorption cross-section (σ PSII ) of PSII photochemistry. Our results clearly indicate that the presently rising temperature adversely affects the photophysiology of natural phytoplankton assemblages in tropical oceans.

Individual variation in metabolic rate, locomotion capacity and hypoxia tolerance and their relationships in juveniles of three freshwater fish species - Xu Pang; De-Yong Pu; Dan-Yang Xia; Xiao-Hong Liu; Shi-Hua Ding; Yun Li; Shi-Jian Fu (Journal of Comparative Physiology B, 2021)

Effect of Partial Root-Zone Drying Irrigation (PRD) on the Gas Exchange and Antioxidant Enzymatic Activities in Alfalfa - Jing Zhang; Hui Xia Liu; Xiao Pan Pang; Cheng Yu; Qian Wang; Yu Pei Zhou; Li Guo Lin; Zheng Gang Guo (Journal of Soil Science and Plant Nutrition, 2019)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Two new alkylated furan derivatives with antifungal and antibacterial activities from the plant endophytic fungus Emericella sp. XL029 - Xia Wu; Xue-Jiao Pang; Lu-Lin Xu; Ting Zhao; Xin-Yu Long; Qiong-Yin Zhang; Hai-Li Qin; Deng-Feng Yang; Xiao-Long Yang (Natural Product Research, 2018)

C21 steroid derivatives from the Dai herbal medicine Dai-Bai-Jie, the dried roots of Marsdenia tenacissima, and their screening for anti-HIV activity - Xu Pang; Li-Ping Kang; Xiao-Mei Fang; He-Shui Yu; Li-Feng Han; Yang Zhao; Li-Xia Zhang; Li-Yan Yu; Bai-Ping Ma (Journal of Natural Medicines, 2018)

Large-scale hatchery of the kelp Saccharina japonica: a case study experience at Lvshun in northern China - Li Su; Shao Jun Pang; Ti Feng Shan; Xia Li (Journal of Applied Phycology, 2017)

Bioorganic fertilizer maintains a more stable soil microbiome than chemical fertilizer for monocropping - Feng Cai; Guan Pang; Rui-Xia Li; Rong Li; Xiao-Long Gu; Qi-Rong Shen; Wei Chen (Biology and Fertility of Soils, 2017)

Transcriptome analysis reveals the potential contribution of long noncoding RNAs to brown adipocyte differentiation - Liang hui You; Li jun Zhu; Lei Yang; Chun mei Shi; Ling xia Pang; Jun Zhang; Xian wei Cui; Chen bo Ji; Xi rong Guo (Molecular Genetics and Genomics, 2015)

Two novel CAII mutations causing carbonic anhydrase II deficiency syndrome in two unrelated Chinese families - Qianqian Pang; Xuan Qi; Yan Jiang; Ou Wang; Mei Li; Xiaoping Xing; Jin Dong; Weibo Xia (Metabolic Brain Disease, 2015)

Effects of Fluoride on DNA Damage and Caspase-Mediated Apoptosis in the Liver of Rats - Guo Hua Song; Fu Bing Huang; Ji Ping Gao; Mao Lin Liu; Wen Biao Pang; Wei bin Li; Xiao Yan Yan; Mei Jun Huo; Xia Yang (Biological Trace Element Research, 2015)

The biological effects of hsa-miR-1908 in human adipocytes - Lei Yang; Chun-mei Shi; Ling Chen; Ling-xia Pang; Guang-feng Xu; Nan Gu; Li-jun Zhu; Xi-rong Guo; Yu-hui Ni; Chen-bo Ji (Molecular Biology Reports, 2015)

De novo transcriptome analysis of the gametophyte of Undaria pinnatifida (Phaeophyceae) - Ti Feng Shan; Shao Jun Pang; Jing Li; Xia Li (Journal of Applied Phycology, 2015)

Complete mitochondrial genome of the brown alga Sargassum horneri (Sargassaceae, Phaeophyceae): genome organization and phylogenetic analyses - Feng Liu; Shaojun Pang; Xia Li; Jing Li (Journal of Applied Phycology, 2015)

Geochemistry and genesis of authigenic pyrite from gas hydrate accumulation system in the Qilian Mountain permafrost, Qinghai, northwest China - PingKang Wang; YouHai Zhu; ZhenQuan Lu; Xia Huang; ShouJi Pang; Shuai Zhang; ShaoQing Jiang; QingHai Li; KaiLi Yang; Bing Li (Science China Earth Sciences, 2014)

Development and preliminary evaluation of a double-cell ozonesonde - Jinqiang Zhang; Yuejian Xuan; Xiaolu Yan; Mingyuan Liu; Hongmin Tian; Xiang’ao Xia; Li Pang; Xiangdong Zheng (Advances in Atmospheric Sciences, 2014)

Supramolecular Interaction of Two Tryptophans with p-sulfonated calix[4,6,8]arene - Tao-Tao Pang; Hai-Long Liu; Li-Ming Du; Yin-Xia Chang; Yun-Long Fu (Journal of Fluorescence, 2014)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Physiological responses to salt stress of T2 alfalfa progenies carrying a transgene for betaine aldehyde dehydrogenase - Li-Ping Yan; Cui-Lan Liu; Hui-Min Liang; Xiu-Hong Mao; Fei Wang; Cai-Hong Pang; Jing Shu; Yang Xia (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)